Neglected aspects of tick-borne rickettsioses - Tomassone, Laura; Portillo, Aránzazu; Nováková, Markéta; de Sousa, Rita; Oteo, José Antonio (Parasites & vectors, 2018)
Rickettsioses are among the oldest known infectious diseases. In spite of this, and of the extensive research carried out, many aspects of the biology and epidemiology of tick-borne rickettsiae are far from being completely understood. Their association with arthropod vectors, the importance of vertebrates as reservoirs, the rarity of clinical signs in animals, or the interactions of pathogenic species with rickettsial endosymbionts and with the host intracellular environment, are only some examples. Moreover, new rickettsiae are continuously being discovered. In this review, we focus on the 'neglected' aspects of tick-borne rickettsioses and on the gaps in knowledge, which could help to explain why these infections are still emerging and re-emerging threats worldwide.
Keywords: Rickettsia Infections; Vertebrate hosts; opomíjené nemoci; nemoci přenášené klíšťaty; Tick-Borne Diseases; zdroje nemoci; Ticks; rickettsiové infekce; Disease Reservoirs; zvířata; Humans; Candidatus; Rickettsia spp.; Neglected Diseases; klíšťata; Epidemiology; lidé; Animals